2015
DOI: 10.1177/0010414014565889
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Marginal Citizens and Voters

Abstract: In this article, we study how social assistance shapes election results across Latin America. Case studies in several countries have found electoral effects, yet it remains unclear whether and how effects vary cross-nationally, and whether electoral effects are due to mobilization or persuasion. We theorize that programs mobilize non-voters and convert the opposition simultaneously, but that the effects vary based on country-level political and programmatic differences. Using 2012 AmericasBarometer data, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(31 citation statements)
references
References 50 publications
(51 reference statements)
2
27
0
Order By: Relevance
“…My results on the importance of the pocketbook channel also differ from the majority of scholarship on economic voting, which tends to emphasize the importance of sociotropic motivations (Kinder & Kiewiet, 1979; Nadeau et al, 2013). These findings add to a small but growing subset of scholarship on economic voting that has found support for pocketbook theories (Healy et al, 2017; Layton and AmySmith 2015; Linos 2013; Murillo & Visconti, 2017; Pop-Eleches and Pop-Eleches 2012). My evidence of pocketbook voting during a currency crisis indicates that pocketbook concerns apply across a wider range of economic policy issues than is often appreciated.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…My results on the importance of the pocketbook channel also differ from the majority of scholarship on economic voting, which tends to emphasize the importance of sociotropic motivations (Kinder & Kiewiet, 1979; Nadeau et al, 2013). These findings add to a small but growing subset of scholarship on economic voting that has found support for pocketbook theories (Healy et al, 2017; Layton and AmySmith 2015; Linos 2013; Murillo & Visconti, 2017; Pop-Eleches and Pop-Eleches 2012). My evidence of pocketbook voting during a currency crisis indicates that pocketbook concerns apply across a wider range of economic policy issues than is often appreciated.…”
Section: Discussionsupporting
confidence: 54%
“…The majority of research concludes that sociotropic economic voting is more prevalent than pocketbook voting (Kinder & Kiewiet, 1979; Nadeau et al, 2013; Singer and Carlin 2013). On the other hand, a small number of recent studies that directly measure changes in household income (Healy et al, 2017; Murillo & Visconti, 2017) and that examine individuals that receive government transfers (Layton and Smith 2015; Linos 2013; Pop-Eleches and Pop-Eleches 2012) find support for the pocketbook theory. This article shows that pocketbook voting is not confined to microeconomic policy issues, such as targeted transfers.…”
Section: Introductionmentioning
confidence: 99%
“…Even before those developments, CCT programs started proliferating in Latin America. Studies found that voters tend to reward governments that implement targeted social assistance programs [77][78][79], at least in the short term [80]. Subsidies for forest conservation can, in addition, also legitimately benefit geographically marginalized rural populations that are otherwise hard to reach for central states.…”
Section: Poverty Reductionmentioning
confidence: 99%
“…First, it challenges the findings from the existing literature on the political behavioral consequences of program conditionalities. Whereas previous research suggests that CCT conditionalities, and means-tested program conditionalities more generally, reduce political participation or have no effect (Layton and Smith 2015;Watson 2015), I utilize an alternative research design to argue that CCT conditionalities spur increased involvement in political activities. Second, the article improves our theoretical understanding of why some means-tested social programs increase political participation, while others have no effect or even a negative effect on participation (Soss 1999;Campbell 2003;Mettler and Stonecash 2008;Bruch, Ferree, and Soss 2010;Garay 2007;Holzner 2010).…”
mentioning
confidence: 99%